2006
DOI: 10.1677/joe.1.06614
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone increases primordial follicle reserve in mature female hypogonadal mice

Abstract: Ovarian primordial follicle reserve is considered hormonally independent or subject to depletion by FSHdriven follicle recruitment. To explore specific in vivo effects of FSH on early follicle populations in the absence of luteinizing hormone (LH) activity, we examined mature hypogonadal (hpg), gonadotrophin-deficient mice expressing transgenic (tg) human FSH. Sustained expression of tg-FSH (5·3 0·3 IU/l) increased ovary weights fourfold and significantly elevated total primordial follicle numbers twofold in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 51 publications
(56 reference statements)
2
27
0
Order By: Relevance
“…For instance, it has been demonstrated that FSH directly regulate bone mass independently of E2 by activating bone resorption and therefore it might be a potential factor involved in Sema4D −/− bone resorption phenotype [24]. In the same way, we did not completely rule out the possibility that Gnrh1 could act directly on osteoclasts, to promote bone resorption, although it has been shown that Gnrh1 have no effect on osteoclastogenesis [24] and that hypogonadism is currently associated with bone loss [26]. In addition to the FSH direct effect on bone, recent studies have reported that elevated FSH levels increase bone formation, independently of E2, and that this increased bone formation is correlated to the FSH induced ovarian secretion of inhibin and androgens [27].…”
Section: Discussionmentioning
confidence: 75%
“…For instance, it has been demonstrated that FSH directly regulate bone mass independently of E2 by activating bone resorption and therefore it might be a potential factor involved in Sema4D −/− bone resorption phenotype [24]. In the same way, we did not completely rule out the possibility that Gnrh1 could act directly on osteoclasts, to promote bone resorption, although it has been shown that Gnrh1 have no effect on osteoclastogenesis [24] and that hypogonadism is currently associated with bone loss [26]. In addition to the FSH direct effect on bone, recent studies have reported that elevated FSH levels increase bone formation, independently of E2, and that this increased bone formation is correlated to the FSH induced ovarian secretion of inhibin and androgens [27].…”
Section: Discussionmentioning
confidence: 75%
“…Serum levels of TgFSH driven by the rat insulin II gene promoter (21,22) were significantly higher in TgFSH H compared with TgFSH m females (Fig. 1A).…”
Section: Tgfsh Stimulates Ovarian Secretion Of Inhibin a And Testostementioning
confidence: 92%
“…Our TgFSH mouse model provides progressively rising circulating levels of FSH with age (18), with distinct transgenic lines allowing dose-dependent analysis of FSH actions in vivo (19)(20)(21). Using this FSH model, we have determined TgFSH actions on bone (i) in isolation of LH actions, using TgFSH expressed in hypogonadal (hpg) female mice lacking gonadotropinreleasing hormone (GnRH) and therefore endogenous FSH and LH secretion (21,22), and (ii) in isolation of intact ovaries, using ovariectomized TgFSH mice (TgFSH-Ovx). In contrast to previous observations, our findings reveal that elevated FSH activity in vivo, regardless of LH and/or estradiol levels, markedly stimulates bone mass via an ovary-dependent pathway.…”
mentioning
confidence: 99%
“…Yet, the number of competent oocytes in hpg mice was reduced markedly, and exogenous gonadotropin increased the number of competent oocytes (57). Accordingly, FSH increased follicular growth in hpg mice (58). Studies with ArKO mice or preantral follicles cultured with an aromatase inhibitor resulted in normal follicular growth, and the oocytes matured in vitro (35,59,60).…”
Section: Discussionmentioning
confidence: 99%